Development of a Contextual Approach-Based Learning Model Through Pusako Kenduri Culture to Improve Environmental Care Attitudes, Communication Skills, and Cognitive Learning Outcomes - Hadi Candra; Nosi Qadariah; Rimin (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2022)
The implementation of learning at the Kerinci Islamic Institute (IAIN) refers to the Indonesian National Qualifications Framework (KKNI). 21st century learning requires students to have a caring attitude towards the environment, communication skills, and cognitive learning outcomes. Observation results show that environmental care attitudes, communication skills, and student cognitive learning outcomes are still low. The formulation of the research problem is how to value the validity, practicality, and effectiveness of the contextual approach-based learning model through the Pusako feast culture. The type of research is development research using the ADDIE design (analyze, design, develop, implement, and evaluate). The logical validation value is 87.58 with a very valid category. The validation value of field practitioners is 89.4% with a very valid category. The value of the practicality of the learning model is 89% with a very practical category. The learning model developed is effective to improve the attitude of caring for the environmentF count 12,407 with p-value = 0.048 < (α = 0.05), skills with p-value = 0.000 < (α = 0.05), and cognitive learning outcomes with p-value = 0.009 < ( = 0.05). The contextual approach-based learning model through the cultural feast of the Satisfaction has been very valid, very practical, and effective for improving environmental care attitudes, communication skills, and cognitive learning outcomes.